Adult T‐cell leukemia–lymphoma in a pregnant woman diagnosed as a human T‐cell lymphotropic virus type 1 carrier. Issue 3 (10th December 2015) - Fuchi, Naoki; Miura, Kiyonori; Imaizumi, Yoshitaka; Hasegawa, Hiroo; Yanagihara, Katsunori; Miyazaki, Yasushi; Masuzaki, Hideaki
Abstract: Human T‐cell leukemia virus type 1 (HTLV‐1) is the causative agent of adult T‐cell leukemia–lymphoma (ATL), which is difficult to cure. In Japan, a nationwide HTLV‐1 screening test in pregnant women has been recommended since 2011. A 30‐year‐old woman was diagnosed as being an HTLV‐1 carrier in her previous pregnancy. During the current pregnancy, she had persistent fever and cough. Although she had treatment with antibiotics, peripheral white blood cell count remained high, with an abnormal lymphocyte count. Given that she was an HTLV‐1 carrier, she was diagnosed with unfavorable chronic ATL (aggressive ATL) at 12 weeks gestation. After pregnancy termination, her ATL status became favorable chronic ATL (indolent ATL). Therefore, watchful waiting was performed until disease progression. This is the first case report of chronic ATL in early pregnancy, in a woman already diagnosed as an HTLV‐1 carrier on screening test.